Natural Information Measures In Cox Approach For Contextual Probabilistic Theories - Holik, Federico Hernán (2016)
In this article we provide, from a novel perspective, arguments that support the idea that, in the wake of Cox? approach to probability theory, von Neumann?s entropy should be the natural one in Quantum Mechanics. We also generalize the pertinent reasoning to more general orthomodular lattices, which reveals the structure of a general non-Boolean information theory.